Association Between the Frailty and New-Onset Atrial Fibrillation/Flutter Among Elderly Hypertensive Patients - Hang, Fei; Chen, Jieruo; Wang, Zefeng; Yan, Jiafu; Wu, Yongquan (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Frailty was common in patients with Atrial fibrillation/flutter (AF), but there was a lack of evidence regarding the relationship between frailty and new-onset AF. Methods: We performed a post-hoc analysis of data from the Systolic Blood Pressure Intervention Trial (SPRINT). We evaluated the relationship between baseline frailty status and new-onset atrial fibrillation/flutter (AF) in elderly hypertensive patients. Results：7316 participants were included in our analysis, with 115 new cases of AF occurring during a mean follow-up of 3.54 years. Using SPRINT frailty index criteria, 1,535 fit, 4,041 less fit, and 1,740 frailty were enrolled. We constructed three Cox models to assess the relationship between frailty and new-onset AF. Participants with frailty had a significantly higher risk of new-onset AF compared with fit group in all models. We combined fit and less fit groups into no frailty group to assess the impact of frailty on new-onset AF, and frailty remained associated with the increased risk of new-onset AF compared with the no frailty group [HR=2.09, 95%CI:( 1.41, 3.09), P<0.001]. We used frailty index as a continuous variable to evaluate the relationship between frailty index and new-onset AF. Smooth curve showed that log HR appeared to increase linearly. And no evidence was found for the interaction of subgroups and frailty for the risk of new-onset AF. Conclusion: This study found frailty was a strong independent risk factor for new-onset AF among elderly hypertensive patients and frailty screening should be considered to prevent AF.